Capitalism after postmodernism : neo-conservatism, legitimacy and the theory of public capital - Wilson, H. T. (International comparative social studies, 2002)
This work addresses issues in the old and new political economy. Going back to Marx, Weber and Habermas, it concludes that social intellectuals still have to rise to the occasion, rather than assisting in the massive self-confirming prophecy that postmodernism threatens to become.